Is the Glass Half Empty or Half Full? Enrollment, Graduation, and Dropout Rates in Latin America - Marina Bassi; Matias Busso; Juan Sebastián Mu\~noz (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
We use 292 household surveys from 18 Latin American countries to document patterns in secondary school graduation rates over the period 1990-2010. We find that enrollment and graduation rates increased during that period while dropout rates decreased. We provide two types of explanations for these patterns. Countries implemented changes on the supply side to increase access, by increasing the resources allocated to education and designing policies to help students staying in school. Despite this progress, graduation rates are still generally low, there still persist remarkable gaps in educational outcomes in terms of gender, income quintiles, and regions within countries, and the quality of education is generally low.
Keywords: I21; I24; O54; 330; Secondary school; graduation; enrollment; dropout; Latin America